SYARIAH BANK EMPLOYEE PERFORMANCE MODEL OF PT. BANK SYARIAH AL SALAAM REGIONAL JAKARTA AND DEPOK - Zainuri, Zainuri; Havidz Aima, Muhammad; Ali Iqbal, Muhammad; Surip, Ngadino (Dinasti International Journal of Digital Business Management, 2021)
This study aims to examine the prophetic leadership and organizational commitment mediated by the motivation that affects employee performance, namely the employee performance of PT Bank Syariah Al Salaam Jakarta and Depok Regional. The research method uses a quantitative approach, with data collection using primary data, secondary data from Personnel Management and library research, primary data using all employees at PT Bank Syariah Al Salaam as many as 80 respondents, from all Jakarta and Depok Regional Divisions. Data collection techniques using interviews and questionnaire instruments. The questionnaire survey instrument was delivered randomly to employees of PT Bank Syariah Al Salaam. Data were analyzed using structural equation modeling (SEM) with the Smart PLS3.0 software program. to test the significance of prophetic leadership and organizational commitment affecting employee performance and mediated by motivation. The results showed that prophetic leadership, organizational commitment and motivation have a significant positive effect on employee performance, either partially or simultaneously. Prophetic leadership as the most important factor influencing employee performance. The managerial implication is that the organization or leader must develop a harmonious work culture and motivation for employees to achieve their best performance. This study reveals that organizational commitment, Prophet Leadership and motivation have a significant positive effect on performance, both partially and simultaneously. Besides that, the motivation partially mediate variable of the Prophet Leadership variable and organizational commitment on performance and has a significant effect.